Social security and retirement reforms in South Africa : prospects and challenges - Kgatla, Itumeleng Peter (University of Limpopo, Turfloop Campus, 2013)
This mini-dissertation discusses South African social security and retirement reforms that will be used as guidelines towards promulgation of the new Pension Funds Act which will incorporate both private and public pensions. These proposals have been highlighted in the Retirement Reform Discussion Paper issued by National Treasury in 2004 and the Social Security and Retirement Reform paper, issued by both National Treasury and Department of Social Development, 2007. Further, the recent discussion papers entitled ‘Strengthening Retirement Savings and a Safer Financial Sector to Serve South Africa Better’ published in 2011 and 2012 respectively have strengthened social security and retirement reforms debate in South Africa. This mini-dissertation will incorporate both social security and retirement reforms.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2013
Keywords: Pension funds; Social security; Social security -- Law and legislation -- South Africa; Retirement income -- Government policy -- South Africa; Pensions -- Law and legislation -- South Africa; Pension trusts